CONCEPTUALIZING PERCEIVED FORM OVER SUBSTANCE (PFOS): A THEORETICAL EMPIRICAL FRAMEWORK FOR UNDERSTANDING EDUCATIONAL PERFORMATIVITY AMONG INDONESIAN PRE-SERVICE TEACHERS - Anita Deka; Dasim Budimansyah; Mupid Hidayat; Momod Abdul Somad (JURNAL EDUSCIENCE, 2026)
Purpose – This study aims to conceptualize and examine Perceived Form Over Substance (PFOS) as a theoretical-empirical framework for explaining why Indonesian pre-service teachers may prioritize administrative form, academic image, and measurable outcomes over substantive pedagogical learning.Methodology – This study employed an exploratory quantitative design. The instrument was developed through preliminary observations, focus group discussions, literature review, and two rounds of pilot testing to refine the theoretical domains. The main survey was administered to 347 pre-service teachers in Indonesia. The final instrument consisted of the PFOS scale, Personal Traits (PTRAIT), and Systemic Pressure (PSIST). Quantitative data were analyzed using Principal Component Analysis (PCA) with Promax rotation, reliability analysis, descriptive statistics, and multiple linear regression.Findings – The results indicate that PFOS comprises three dimensions: Academic Formalism, Image Management, and Outcome Orientation. The factor structure was empirically supported by KMO = 0.86, Bartlett’s test p < 0.001, and total variance explained of 45.47%. The PFOS scales demonstrated satisfactory reliability, with Cronbach’s alpha ranging from 0.71 to 0.76. Regression results indicate that systemic pressure, particularly procedural certainty and task structure, is the strongest and most consistent predictor of all PFOS dimensions. Thus, PFOS is better understood as an adaptive response to academic systemic pressures rather than a deficit in individual character.Contribution – This study contributes to educational performativity literature by proposing PFOS as a multidimensional construct in Indonesian teacher education. It offers practical insights for evaluation systems that support autonomy, pedagogical meaning, and substantive learning.